Analisis Persepsi Masyarakat tentang Dampak Penambangan Pasir di Sungai Mujur dan Sungai Regoyo - Sari, Ike Kumala; Sudarti, Sudarti (CV. Social Politic Genius (SIGn), 2021)
Sand mining is an activity of exploiting natural resources below the surface of the ground that can be carried out underground river flows to extract minerals, namely sand. Sand mining is generally carried out to increase development. This activity has a positive impact on the community. However, if you ignore the environmental impact analysis, it will harm the community, which can cause environmental damage. Therefore, this study aims to analyze public perceptions of the impact of sand mining on the Mujur River and the Regoyo River. The research method used is a survey and data obtained by conducting observations, documentation, and questionnaires. Respondents in this study amounted to 30 people who are the surrounding community. For one month, this research was conducted around the Mujur River and the Regoyo River, Pasirian District, Lumajang Regency, East Java. The data of this study were analyzed using descriptive analysis. This study indicates the high public perception of the impact of sand mining on the Mujur River and Regoyo River, seen from the percentage of the questionnaire calculation, which is divided based on the positive and negative impacts of sand mining on the Mujur River and Regoyo River.